Evaluation of Applied Destructive and Non-destructive Tests in the Technical Inspection Process of High-Frequency Electric Resistance Weld Pipes - Meysam Rasooly; Masoud Shahi (e-Journal of Nondestructive Testing)
Ensuring the absence of structural defects in metal pipes of the gas network requires production control and quality control tests. On the other hand, the main role of these pipes is the transmission of natural gas, therefore, the smallest leakage, along with damage to the environment and loss of natural gas, entails the dangers of explosion. In this article, all the quality tests performed on the raw materials and the metal pipe production process are mentioned, and the result of their optimization in terms of sampling, prototyping, and acceptance criteria in the quality control plan is given. In addition to destructive tests, three important non-destructive methods including industrial radiography, ultrasonic test, and eddy current test have been specially investigated. The statistical results of detectable defects for three specific sizes of pipes including 4, 6, and 8 inches have been collected. The final result of this essay is the optimization of high-frequency electric resistance welding pipe production.